The use of rumour in tacitus' annals (2013)
The Roman historian, Tacitus, is well-known for his colourful and dramatic narratives, which are observable in his juxtaposition of facts and motives. This is particularly manifest in Annals, and the style has brought the charge of anger, bias and error in writing history against him. This article relates how Tacitus’ portrayal of his characters is evidently prejudiced by his experience of tyranny, corruption and decadence under Domitian’s reign of terror, as well as how the training he received as a rhetorician accounts for the rhetorical and literary treatment of material to realise the objective of preserving the past. The article further notes that the historian scrupulously distinguishes fact from rumour to impress his viewpoints and judgment on readers’ minds. Yet, his use of rumour as a literary device in expressing bias is considered an inevitable part of any historical work, as well as an effective tool in allowing the public to pass judgement on what may be missing in ‘official’ account or possibly wittingly or unwittingly tampered with by those in position of authority. Although Tacitus was not a researcher in the modern sense, the article concludes with a justification that he can still be trusted as a reliable historian who has not descended into wholesale fabrication.